Cartas manuscritas do século XVIII : aspectos filológicos e linguísticos - Silva, Kênia Maria Corrêa da (2013)
This paper aims to research, under philological perspective, 37 handwritten letters, dated from 1713 to 1800, mostly referring to Cuiaba and Mato Grosso captainship, written in several locations, in Brazil and in Portugal, 15 beloging to Mato Grosso Public Archiv (APMT in Portuguese) and 22 to the Mato Grosso Historic and Geographical Institute (IHGMT in Portuguese). Fac-similar and semidiplomatic editions will be made, whereof paleographic aomments will be made, in order to expose aspects of writing with approach to the Brazilian colonial period, especially, facts on Cuiaba and Mato Grosso, region, characterized as Rural Cultural Area, describe orthographical aspects, its variations and phonological correspondences on eighteenth century Portuguese language. For such studies, the bibliographical references that will be used are Spina (1977), Cambraia (2005), Mattos e Silva (2006), among others.